2022
DOI: 10.1016/j.jhep.2021.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of SARS-CoV-2 vaccination in liver transplanted patients: The debate is open!

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 5 publications
4
61
2
Order By: Relevance
“…Moreover, the peak of responder patients J o u r n a l P r e -p r o o f was reached four months after the second vaccine dose and remained stable up to six months. Recent reports indicated that the rate of antibody response to anti-SARS-CoV-2 vaccination in LT patients ranged from 45.5% to 82% 11,12,16,[18][19][20][21][22] , which is comparable to what we observed. However, all these studies evaluated the early (up to 3 months) immune response to vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the peak of responder patients J o u r n a l P r e -p r o o f was reached four months after the second vaccine dose and remained stable up to six months. Recent reports indicated that the rate of antibody response to anti-SARS-CoV-2 vaccination in LT patients ranged from 45.5% to 82% 11,12,16,[18][19][20][21][22] , which is comparable to what we observed. However, all these studies evaluated the early (up to 3 months) immune response to vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…We found conflicting results regarding the impact of time since transplantation on vaccine response: seven studies found higher non-response rates or lower antibody titres in patients with recent transplantation, Rozen-Zvi et al. [ 138 ] found a longer time from transplantation was associated with lower antibody titres [ 21 , 62 , 79 , 139 , 141 , 143 , 155 , 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in solid organ transplant recipients that analyzed immunogenicity following 2 doses of COVID-19 mRNA vaccines have demonstrated suboptimal humoral immune response 47 . However, few studies that looked at vaccine efficacy exclusively in LT recipients have shown mixed results 48 , 49 , 50 . One study involving 161 LT recipients (53% received Pfizer and 47% received Moderna) reported a robust immune with 81% of participants producing detectable antibodies 30 days after the second shot 48 .…”
Section: Sars-cov-2 Vaccinesmentioning
confidence: 99%